Chemometric evaluation of hypericin and related phytochemicals in 17 in vitro cultured Hypericum species, hairy root cultures and hairy root‐derived transgenic plants. (19th July 2017) - Nigutová, Katarína; Kusari, Souvik; Sezgin, Selahaddin; Petijová, Linda; Henzelyová, Jana; Bálintová, Miroslava; Spiteller, Michael; Čellárová, Eva
Abstract: Objectives: The objective of this study was to ascertain the presence and correlations among eight important secondary metabolites viz. hypericin, pseudohypericin, emodin, hyperforin, rutin, hyperoside, quercetin and quercitrin in different organs of 17 in vitro cultured Hypericum species, along with H. tomentosum and H. tetrapterum hairy root cultures, and hairy root‐derived transgenic plants of H. tomentosum . Methods: Samples were extracted and analysed by LC‐MS. The LC‐MS data were subjected to chemometric evaluations for metabolite profiling and correlating the phytochemical compositions in different samples. Key findings: Hypericin, pseudohypericin and their proposed precursor emodin were detected in various levels in the leaves of eight Hypericum species. The highest content of hypericins and emodin was found in H. tetrapterum, which contains the studied secondary metabolites in all plant organs. A significant positive correlation between hypericins and emodin was observed both by principal component analysis (PCA) and multidimensional scaling (MDS), indicating the role of emodin as a possible precursor in the biosynthetic pathway of hypericins. Flavonoids were found in all tested plant organs except roots of H. pulchrum . The hairy roots lacked hypericin, pseudohypericin, emodin, hyperforin and rutin. However, the hairy root‐derived transgenic plants showed a significant increase in flavonoids. Conclusions: This study broadens knowledge about the phytochemical composition of selected in vitro cultured Hypericum species, compared to that of hairy root cultures and hairy root‐derived transgenic plants.